The Effect of Fiscal Decentralization, and Financial Performance on Economic Growth of Mataram City, Indonesia - Zilvi Irta Rizkita; Abdul Manan; Siti Sriningsih; Aloysius Ajab Amin; Yevheniia Sribna; Vesna Aleksić (Journal of Social and Humanities, 2024)
This study aims to analyze the effect of fiscal decentralization and financial performance on economic growth in Mataram City. The data used is secondary data from 2010 to 2022 sourced from BKD. The research approach uses an associative quantitative approach. The data analysis technique used is the analysis of fiscal decentralization, financial performance in the efficiency ratio and effectiveness ratio indicators and using the Eror Corection Model (ECM) statistical test analysis tool. The results showed that the average fiscal decentralization for 13 years in the criteria was sufficient at 37.62%, and has not been able to manage its own finances so that it still depends on local governments even though the source of PAD is starting to improve, while in financial performance with the efficiency ratio indicator that it is quite efficient with an average of 83.73% for 13 years and in the effectiveness ratio indicator that is effective with an average of 96.62% for 13 years. While in the Error Corection Model (ECM) statistical test, that fiscal decentralization has a positive and significant effect at 5% alpha on the economic growth of Mataram city in the short term while in the long term it is not significant at 5% or 10% alpha because the probability value is 0.1323 but has a positive effect, besides that financial performance in the efficiency ratio indicator and the effectiveness ratio has a positive and significant effect at 5% alpha both in the long and short term on the economic growth of Mataram city.